Attitude to the Category of Harmony in Folk Poetry (From the Point of View of Islam) - Guliyev, Fakhraddin (Scholarya Demo Journal of Ruby, 2021)
The article is devoted to the study of the category of "harmony" in the folk poetry of Azerbaijan from the standpoint of the religious worldview. The dialectical nature of harmony, its forms of manifestation in the hierarchy of man-society-universe are examined as well as the scientific and philosophical significance of thoughts about harmony in the work of ashugsozans is indicated. Comparative analysis of scientific, philosophical and religious approaches to the category of harmony allows you to more deeply understand harmony as a complex phenomenon. While science primarily explores the visible aspects of phenomena and objects by generalizing the outcomes of experiments, religion focuses on the invisible sides of the phenomena of reality. Divine order, according to Islamic teachings, is the foundation of harmony in man and the universe. According to this logic, the universe the earth, the sky were created by the divine will, and the trajectories of the sun and moon were predetermined by Him from the very beginning. God created man to be the most beautiful and perfect of all living beings, as well as the most worthy one on the planet. Man is likewise regarded as the center of the cosmos in anthropocentric teaching. Thoughts about harmony in the folk poetry of Azerbaijan correspond to the Islamic doctrine of divine order and to substantiate this position, they refer to the corresponding verses of the holy Koran. In the ashug poetry, the creation of the universe is presented as a result of the divine will, i.e. the ninth heaven and its lower layers are founded, and the movements of the moon and sun received their order. The physical and spiritual aspects of a harmonious person complement each other, and his behaviors and goals are in sync. Ashugi-ozans in poetic language convince readers of the important role of the norms of Islamic ethics in the formation of a harmonious and perfect person. If the harmonious development of society is determined by moral principles, then oral folk poetry is rich in poems, which describe the love of the people for such virtues as justice, courage and generosity, as well as their importance in the formation of harmonious relations between people. Purpose: Study of the category of harmony in folk poetry from the standpoint of a religious worldview. Methodology: Joint application of historical and logical methods and Islamic worldview. Scientific novelty: The category of harmony is investigated on the basis of a comparative analysis of the Islamic worldview as well as scientific and philosophical concepts.